Transgressing the pathos of disability in the films Black and CODA - Aniva Sukul; Atri Majumder; Gyanabati Khuraijam (Social Sciences and Humanities Open, 2025)
Disability, as the idea suggests, is always concerned with issues like physical, mental and psychological impairments, and only a handful of films have projected this issue with the solemnity that it demands. This study will explore Sanjay Leela Bhansali's renowned film Black (2005) and Sian Heder's Oscar winning film CODA (2021), movies which focus highly on the representations and implications of deformed bodies, and the predicament of their condition. Sanjay Leela Bhansali intricately weaves the idea of disability that occupies an enigmatic position as the non-dis-abled are pushed to the margins in order to analyse the things from the disabled point of view. On the other hand, CODA (2021) garnered worldwide critical acclaim for its vivid portrayal of the coming-of age of Ruby, a talented singer and the only hearing member in a deaf family. Black and CODA uniquely represent the pity and pathos attached with disfigured bodies, and they indicate that being different is not a problem at all, rather being perceived as different is symptomatic of an exclusionary politics, which belittles and denies any holistic/stabilized notion of identity to disabled bodies. The pathos is transcended and even to some extent aestheticized by the ineffable spectrum of emotions that juxtaposes and puts into sharp relief the silent and musical world of Ruby, and the dark yet intensely animated microcosm of Michelle. This paper would delineate the representation of disabled identities in these films and trace the transgressive narrative arcs of the disabled characters that shatter the stereotypes.